Kepemimpinan Nasional Dan Peran Militer Dalam Proses Demokratisasi - Riswandha Imawan (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
In response to a widespread pressure for political reform, the military has abandon its predominant role in Indonesian politics in the past Yet the incompetence of civilian politician to govern a deep and extensive conflict embedded within the process of democratization, paradoxically, has driven the need for inviting a military "came back". While positively supporting the military attempt to be politically impartial, this article itemizes four agendas: (1) for recruiting national leaders which are, on the one hand, democratic, but on the other hand, decisive, (2) engaging in a trust-building process among various factions; (3) institutionalization of political mechanism which is effective in handling conflict of interests, and (4) creating a more open political recruitment Under its new paradigm, the military suits to facilitate those processes to take place.